PENGUATAN SPIRITUALITAS MELALUI PRAKTIK WIRID BULANAN PERSPEKTIF PENDIDIKAN AGAMA ISLAM TERHADAP PENGUATAN IMAN, TAKWA, SERTA AKHLAK MULIA DI SMA 4 PARIAMAN - Hamzah Irfanda; Aryogo Adi Guna (Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the strengthening of adolescent spirituality through the practice of monthly wirid from the perspective of Islamic Religious Education towards the development of faith, piety, and noble character at Pariaman 4 State Senior High School. The background of this study is the importance of presenting a sustainable religious program as a space for internalizing divine values ​​for students in the phase of adolescent development that is vulnerable to moral and identity shocks. This study uses a qualitative approach with the ABCD method. The results show that the practice of monthly wirid can strengthen adolescents' transcendental awareness by increasing their understanding of religious teachings, appreciation of spiritual values, and habituation to structured worship. This activity also has an impact on the formation of attitudes of discipline, mutual respect, and the ability to control oneself in social interactions within the school environment. In conclusion, the practice of monthly wirid functions as an effective instrument in strengthening students' spirituality while forming character based on faith, piety, and noble character, making it worthy of being developed as a routine program integrated into school religious development.